Properties of nanosized ZnO:Ho films deposited using explosive evaporation - Kаsumov, А.М.; Strelchuk, V.V.; Kolomys, О.F.; Bykov, О.І.; Yukhymchuk, V.О.; Zahornyi, М.М.; Kоrotkov, K.А.; Kаravaieva, V.М.; Kоrychev, S.F.; Ievtushenko, А.І. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
The properties of nanosized ZnO:Ho thin films deposited by the explosive evaporation method have been studied. This work is aimed at studying the effect of high deposition rate on the oxide characteristics of interest from the viewpoint of photocatalysis, namely: morphology and structure, electrical and optical properties, and lifetime of charge carriers. Explosive deposition of films defines the novelty of this work as compared to the majority of previous studies devoted to nanosized ZnO:Ho photocatalysts, which used equilibrium methods for their synthesis. Methods of scanning electron microscopy, XRD analysis, photoluminescence, and Raman scattering have shown that in ZnO:Ho films deposited using explosive evaporation, with increasing holmium content, amorphization of their structure and morphology is observed. It is related to the random incorporation of holmium atoms into the crystalline lattice of ZnO, as well as with the fact that the ionic radius of Ho³⁺ exceeds that of Zn²⁺. It is accompanied by a shift of the edge of ZnO absorption toward the long-wave (blue) spectral range, the decrease of the bandgap, as well as an increase in the resistivity and lifetime of charge carriers. All these changes are favourable for the photocatalytic process involving nanostructures based on ZnO:Ho. Досліджено властивості нанорозмірних плівок ZnO:Ho, нанесених вибуховим випаровуванням. Метою даної роботи є вивчення впливу великої швидкості осадження на характеристики даного оксиду, які використовуються для процесу фотокаталізу, такі як морфологія і структура, електричні та оптичні властивості, час життя носіїв заряду. Вибухове осадження плівок зумовлює новизну даної роботи стосовно більшості попередніх досліджень нанорозмірних фотокаталізаторів ZnO:Ho, де було використано рівноважні методи їх синтезу. Методами скануючої електронної мікроскопії, рентгеноструктурного аналізу, фотолюмінесценції та раманівського розсіяння показано, що при вибуховому нанесенні плівок ZnO:Ho зі збільшенням вмісту лігатури спостерігається аморфізація їх структури і зміна морфології, які пов’язані з хаотичним вбудовуванням атомів Но в кристалічну ґратку ZnO, а також перевищенням іонного радіуса Ho³⁺ над Zn²⁺. Аморфізація супроводжується зсувом краю поглинання ZnO у довгохвильову (синю) область спектра, зменшенням ширини його забороненої зони, зростанням питомого опору та часу життя носіїв заряду. Всі ці зміни є сприятливими для процесу фотокаталізу за участю наноструктур на основі ZnO:Ho.